Use of Empirical Tools/Calculatrs to Quantify GHG Emission from Agricultural Systems - Sapkota, Tek Bahadur (2017)
The Climate Food and Farming (CLIFF) Research Network is an international research network that helps to expand young researchers' knowledge and experience working on climate change mitigation in smallholder farming. CLIFF provides grants for selected doctoral students to work with CGIAR researchers affiliated with the Standard Assessment of Mitigation Potential and Livelihoods in Smallholder Systems (SAMPLES) project. This presentation is Use of Empirical Tools/Calculatrs to Quantify GHG Emission from Agricultural Systems by Tek B. Sapkota, a scientist with the International Maize and Wheat Improvement Center.